Pengembangan Supporting System Berbasis Teknologi Pada Kafe Traktir Kopi - Liana Oyi Aulia Rachmansyah; Micky Prihanjaya Mocka; Melani Putri Rahmadani (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to examine and develop a technology-based supporting system by utilizing the Loyverse application to support operations at Traktir Kopi Cafe. In the digital era, the implementation of Management Information Systems (MIS) has become a primary pillar for MSMEs to transform conventional business models into modern ones through accurate data processing and overall operational efficiency. The primary issue identified prior to development was the reliance on manual methods prone to human error and the functional limitations of the free version of Loyverse, such as non-real-time stock recording and lack of detailed sales reports. The research methodology employs a descriptive qualitative method with a survey approach and Project-Based Learning (PjBL) stages. Data were collected through field observations, documentation, and in-depth interviews with employees at the Traktir Kopi location in Srengseng Sawah. The results indicate that upgrading the Loyverse system to the paid version provides a significant impact, including automated stock management, comprehensive sales reports for turnover analysis, and more structured employee performance monitoring. In conclusion, developing a technology-based supporting system through Loyverse not only accelerates transaction processes but also serves as a strategic data center that supports managerial decision-making and enhances customer satisfaction through more personalized and efficient service